Chlamydia trachomatis Screening and Treatment in Pregnancy to Reduce Adverse Pregnancy and Neonatal Outcomes: A Review - Adachi, Kristina N.; Nielsen-Saines, Karin; Klausner, Jeffrey D. (Frontiers in Public Health, 2021)
Chlamydial trachomatis infection has been associated with adverse pregnancy and neonatal outcomes such as premature rupture of membranes, preterm birth, low birth weight, conjunctivitis, and pneumonia in infants. This review evaluates existing literature to determine potential benefits of antenatal screening and treatment of C. trachomatis in preventing adverse outcomes. A literature search revealed 1824 studies with 156 full-text articles reviewed. Fifteen studies were selected after fulfilling inclusion criteria. Eight studies focused on chlamydial screening and treatment to prevent adverse pregnancy outcomes such as premature rupture of membranes, preterm birth, low birth weight, growth restriction leading to small for gestational age infants, and neonatal death. Seven studies focused on the effects of chlamydial screening and treatment on adverse infant outcomes such as chlamydial infection including positive mucosal cultures, pneumonia, and conjunctivitis. Given the heterogeneity of those studies, this focused review was exclusively qualitative in nature. When viewed collectively, 13 of 15 studies provided some degree of support that antenatal chlamydial screening and treatment interventions may lead to decreased adverse pregnancy and infant outcomes. However, notable limitations of these individual studies also highlight the need for further, updated research in this area, particularly from low and middle-income settings.